2013
DOI: 10.1371/journal.pone.0084266
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and Consequences of Developmental Acceleration in Tadpoles Responding to Pond Drying

Abstract: Many amphibian species exploit temporary or even ephemeral aquatic habitats for reproduction by maximising larval growth under benign conditions but accelerating development to rapidly undergo metamorphosis when at risk of desiccation from pond drying. Here we determine mechanisms enabling developmental acceleration in response to decreased water levels in western spadefoot toad tadpoles (Pelobates cultripes), a species with long larval periods and large size at metamorphosis but with a high degree of developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
118
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(129 citation statements)
references
References 66 publications
7
118
1
3
Order By: Relevance
“…Our experiment mimics an extreme, but natural and frequent situation, i.e. the end of pond drying (see also [24] for a similar setting). The fact that very few newts metamorphosed in the high water level treatment-which remains relatively low in comparison with the range of values found in the field [35]-is likely adaptive.…”
Section: (A) Environmental Drivers Of Paedomorphosismentioning
confidence: 99%
See 1 more Smart Citation
“…Our experiment mimics an extreme, but natural and frequent situation, i.e. the end of pond drying (see also [24] for a similar setting). The fact that very few newts metamorphosed in the high water level treatment-which remains relatively low in comparison with the range of values found in the field [35]-is likely adaptive.…”
Section: (A) Environmental Drivers Of Paedomorphosismentioning
confidence: 99%
“…Their expression in populations depends on the advantages of living in the aquatic and terrestrial habitats [4]. Because environmental cues play an important role in pushing amphibian larvae to metamorphose in most species [2,23,24], environmental variations are supposed to maintain the two phenotypes in populations because each one is adapted to specific conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated corticosteroid levels may interact with the immune system and act as immunostimulants, although chronically high expression of corticosteroids leads to immunosuppression (Dhabhar , Martin ). As rapidly developing, compensating tadpoles are expected to have higher corticosteroid concentrations (Gomez‐Mestre et al ), it seems possible that their immune defence could be compromised. The only study we are aware of that examined amphibian immune response in relation to growth and development found that accelerated development in response to pond desiccation risk reduced immune response in postmetamorphic wood frogs (Gervasi and Foufopoulos ).…”
mentioning
confidence: 99%
“…As previously stated, CORT induces apoptosis of lymphocytes in many organisms and spikes during amphibian metamorphic climax (Rollins‐Smith et al., ; Rollins‐Smith, ; Verburg‐Van Kemenade et al., ). Thus, exposure to high CORT levels earlier than normal is predicted to cause premature immunosuppression in developing amphibian larvae (Rollins‐Smith and Blair, ; Rollins‐Smith, ; Gomez‐Mestre et al., ). We observed fewer leukocytes/μg spleen in Experiment 1 GS 36 and post‐meta individuals reared in a declining versus constant water environment, with a greater difference in Group 2 tadpoles.…”
Section: Discussionmentioning
confidence: 99%
“…Although corticosterone (CORT) can aid in expediting amphibian metamorphosis, numerous studies have revealed a decrease in metamorphic size with accelerated development (Hayes and Licht, ; Wright et al., ; Glennemeier and Denver, ). This type of phenotypic plasticity is present in many amphibian species, but can have trade‐offs (Newman, ; Gray and Smith ; Gervasi, ; McMurry et al., ; Gomez‐Mestre et al., ; Warne and Crespi, ). These carryover effects can have direct influence on body size, survival, immunocompetence, and fitness potential of juvenile frogs and can potentially remain into adulthood (Chelgren et al., , ; Boes and Bernard, ; Crespi and Warne, ; Krynak et al., ; Tarvin et al., ; Warne and Crespi, ).…”
Section: Introductionmentioning
confidence: 99%